Characterization and fabrication of bio-composite filaments for fused deposition modeling 3D printing - P. Phengchan (2020)
© Published under licence by IOP Publishing Ltd. The metal bone screws are generally used in bone fractures. The bio-composite bone screws will be fabricated soon by using hydroxyapatite (HA) to reinforce polylactic acid (PLA) and polycaprolactone (PCL) filament for 3D printing. In this study aimed to characterize morphological and physical properties of bio-composite filaments. HA was synthesized from bovine bone. X-ray diffraction analysis indicated that the obtained HA and HA standard showed a similar chemical composition. The morphological observation of bio-composite filaments by scanning electron microscope (SEM) revealed the distribution of HA in bio-composite filaments. The elemental composition of the filament by energy dispersive spectrometer indicated the consisting of calcium, carbon and oxygen elements. The diameter measurement of all bio-composite filaments indicated the values ranged from 1.66 to 1.86 mm which were non-significantly different value in each composite filament and similar with a filament standard.